2016
DOI: 10.3171/2015.4.spine131119
|View full text |Cite
|
Sign up to set email alerts
|

What would be the annual cost savings if fewer screws were used in adolescent idiopathic scoliosis treatment in the US?

Abstract: OBJECT There is substantial heterogeneity in the number of screws used per level fused in adolescent idiopathic scoliosis (AIS) surgery. Assuming equivalent clinical outcomes, the potential cost savings of using fewer pedicle screws were estimated using a medical decision model with sensitivity analysis. METHODS Descriptive analyses explored the annual costs for 5710 AIS inpatient stays using discharge d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Another recent study by Larson et al (26) and the Minimize Implants Maximize Outcomes Study Group estimated the amount of cost savings by utilizing the KIDS database for AIS surgery and other retrospective studies on screw position. The authors concluded that a modest reduction in pedicle screw use could reduce the national costs of AIS surgery by up to 7% (26).…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study by Larson et al (26) and the Minimize Implants Maximize Outcomes Study Group estimated the amount of cost savings by utilizing the KIDS database for AIS surgery and other retrospective studies on screw position. The authors concluded that a modest reduction in pedicle screw use could reduce the national costs of AIS surgery by up to 7% (26).…”
Section: Resultsmentioning
confidence: 99%
“…Behrbalk et al observed 21 Scheuermann kyphosis patients and concluded that the low screw density technique reduced the implant-related cost by 32%; meanwhile, it achieved safe and effective outcomes on a par with the high screw density technique [ 29 ]. In addition, Larson et al explored the national inpatient database in the United States and found that by changing the HD screw pattern to an LD pattern, the total cost of AIS surgery would effectively be reduced by $11 million to $20 million [ 30 ]. In our study, no significant differences were found in the SRS-22 scores between the two groups at the time of the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…24 Besides screw malplacement issues, the extra costs of unnecessary screws could increase cost-effectiveness of spinal instrumentation. 25 The presented model was not sufficient to determine a significant difference in the stress on adjacent segments, but indicated no increased fracture displacement risk with fewer screws.…”
Section: Skipped Level Instrumentationmentioning
confidence: 80%